OVERVIEW OF THE DEVELOPMENT OF STUNTING CHILDREN AGED 2-5 YEARS IN GEDOG VILLAGE - Faradillah Nur Aulya Rahmah; Dewi Rachmawati; Tri Cahyo Sepdianto (Universitas Karya Husada Semarang, 2024)
Stunting is a growth and development problem that has an impact on intellectual abilities, decreased economic productivity and the risk of metabolic diseases which will affect the development of children in the future. The purpose of this study was to determine the development of stunted children aged 2-5 years in Gedog Village. This research design uses descriptive quantitative with a sample size of 42 stunted children aged 2-5 years who meet the inclusion criteria and are selected using purposive sampling method. Data collection was carried out on February 7-29, 2024 at each integrated healthcare center in Gedog Village. Instruments in the study using the Denver Development Screening Test I and results of the DDST assessment are normal, abnormal, suspect, and unstable. The data obtained is presented in the form of diagrams and narrated. The results of this study were gross motor development 75% scored normal and 25% scored advanced, fine motor development 69% of children were normal, 22% delay and 8% caution, language development 53% normal, 39% caution and 8% delay, personal social development 47% normal, 47% delay and 6% caution and overall normal results 53%, Abnormal 19% and suspect 28%. From these results, it is found that stunting is not the main cause of developmental abnormalities in children. Parenting and the environment are also one of the factors that make children reach their developmental stage.